Adherence to the Mediterranean dietary pattern and mental health outcomes in Hong Kong adults: a cross-sectional study - Fiona Yan-Yee Ho; Vincent Wing-Hei Wong; Bryant Pui-Hung Hui; Adrienne O’Neil; Wolfgang Marx (BMC Public Health, 2026)
Abstract Background Adherence to the Mediterranean dietary pattern (MDP) has been associated with lower depressive, anxiety, and insomnia symptoms, yet associations with stress, health-related quality of life (HRQoL), and functional impairment, as well as those of individual MDP components, remain underexplored in Chinese adults. Methods A cross-sectional survey of 1,355 Hong Kong adults examined associations between MDP adherence and depressive, anxiety, and insomnia symptoms, perceived stress, HRQoL, and functional impairment. Hierarchical linear regression compared moderate-to-high with low MDP adherence, adjusting for sociodemographic and lifestyle covariates. Analyses of individual dietary components were exploratory. Results Compared with low adherence, moderate-to-high MDP adherence was associated with lower depressive (B = -0.79, 95% CI -1.34 to -0.25), anxiety (B = -0.71, 95% CI -1.25 to -0.17), and insomnia symptoms (B = -0.66, 95% CI -1.29 to -0.03), and perceived stress (B = -1.50, 95% CI -2.47 to -0.54), and better HRQoL (B = 0.03, 95% CI 0.01 to 0.04), but not functional impairment. Exploratory analyses indicated that higher vegetable consumption was associated with lower anxiety and insomnia symptoms and better HRQoL, whereas lower sweetened drink, commercial sweets and pastries, and butter, margarine, or cream consumption with lower insomnia symptoms, perceived stress, and functional impairment, respectively. No component was significantly associated with depressive symptoms. Conclusions Higher MDP adherence was associated with more favorable mental health outcomes and better HRQoL. Findings may inform culturally informed dietary intervention research aimed at evaluating potential effects on mental health. The non-probability sample and cross-sectional design limit generalizability and preclude causal inference.